2019
DOI: 10.1111/jph.12874
|View full text |Cite
|
Sign up to set email alerts
|

Baseline sensitivity of Fusarium graminearum from wheat fields in Henan, China, to metconazole and analysis of cross resistance with carbendazim and phenamacril

Abstract: The filamentous plant pathogenic fungus Fusarium graminearum is one of the most important pathogens causing Fusarium head blight (FHB) in wheat in the Henan Province of China. Metconazole is among the demethylation inhibitor (DMI) fungicides with a higher inhibitory activity on the mycelial growth of F. graminearum. In 2016 and 2017, 119 single spore isolates of F. graminearum, prior to being exposed to metconazole, were recovered from 52 wheat fields near 11 cities in Henan Province. The inhibitory activity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 45 publications
(80 reference statements)
0
9
0
Order By: Relevance
“…The average EC 50 value for mycelial growth of 100 F. graminearum isolates was 0.019 ± 0.007 μg/mL. To our knowledge, the mean EC 50 value for quinofumelin-inhibiting mycelial growth of F. graminearum was lower than phenamacril, tebuconazole, carbendazim, metconazole, and epoxiconazole [ 12 , 17 , 18 , 31 , 32 ]. Previous studies reported that Quinone outside inhibitors (QoIs) and Succinate dehydrogenase inhibitors (SDHIs) had good effects in the control of FHB.…”
Section: Discussionmentioning
confidence: 95%
“…The average EC 50 value for mycelial growth of 100 F. graminearum isolates was 0.019 ± 0.007 μg/mL. To our knowledge, the mean EC 50 value for quinofumelin-inhibiting mycelial growth of F. graminearum was lower than phenamacril, tebuconazole, carbendazim, metconazole, and epoxiconazole [ 12 , 17 , 18 , 31 , 32 ]. Previous studies reported that Quinone outside inhibitors (QoIs) and Succinate dehydrogenase inhibitors (SDHIs) had good effects in the control of FHB.…”
Section: Discussionmentioning
confidence: 95%
“…Among them, FHB is the most harmful to wheat. In recent years, with the transformation of modern agriculture and the impact of global warming, F. graminearum has caused serious economic losses to wheat production of the world (Liu, Fu, et al., 2020; Liu et al., 2019; Liu, Liu, et al., 2020; McKay et al., 2019; Xu & Nicholson, 2009). FHB can lead to the decline of wheat grain quality and produce mycotoxins (for instance, 3‐acetyl‐deoxynivalenol, 15‐acetyl‐deoxynivalenol, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…FHB can lead to the decline of wheat grain quality and produce mycotoxins (for instance, 3‐acetyl‐deoxynivalenol, 15‐acetyl‐deoxynivalenol, etc.) in the susceptible grains, which may cause human and animals poisoning (Duan et al., 2018; Liu, Fu, et al., 2020; Liu et al., 2010, 2019; Liu, Liu, et al., 2020; McKay et al., 2019; Pasquali et al., 2020; Qu et al., 2008; Yan et al., 2020; Yin et al., 2009). In China, FHB is common in regions with mild climate and high humidity such as several major river basins (Hao et al., 2017; Liu, Fu, et al., 2020; Liu et al., 2019; Liu, Liu, et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations